A Critical Assessment of Endoscopic Third Ventriculostomy Results an In-depth Analysis of Children (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Background: The endoscopic ventriculostomy of the third ventriculostomy is a surgical procedure offered to children and adults diagnosed with obstructive or non-communicating hydrocephalus. Objective: This study assessed and analyzed the surgical outcomes of children who underwent endoscopic third ventriculostomy (ETV). Patients and methods: 115 pediatric patients with hydrocephalus, whose ages ranged from less than three months to 13 years, were recruited. Clinical data for the third ventriculostomy procedure were collected from different hospitals in Iraq in the period from January 14, 2022, to September 28, 2023, where patients’ clinical data included all of the causes resulting from hydrocephalus, the duration of the operation, the duration of follow-up and recovery, the success and failure rate of the operation, the length of stay in the hospital, the complication rate, and the patient’s quality of life. Results: Our results show that demographic data of children patients shows that children aged 7–13 years had the highest rate, which included 50 cases, while males had the highest rate, which included 74 cases compared with 41 cases for females, as well as causes of hydrocephalus, whose most common prevalence was stenosis of the cerebral aqueduct, which included 40 cases, and brain tumors, which included 49 cases. We enrolled clinical findings of children who underwent an ETV procedure surgically, where the time of endoscopic third ventriculostomy was 1.46 ± 0.21, the length of stay in hospital was 2.80 ± 1.02 days, successful access to surgery included 104 patients, failed access to surgery included 11 cases, and the rate of complications was 25.22% of total patients, which included CSF leaks in 9 cases, hyponatremia in 6 cases, and pseudo meningocele in 5 cases. Conclusion: This study indicated that endoscopic third ventriculostomy (ETV) is the safest and most effective surgical procedure in the treatment of pediatric patients with hydrocephalus, which results in a high success rate for the operation and results in the recovery of pediatric patients.